Neonicotinoid Pesticides Cause Mass Fatalities of Native Bumble Bees: A Case Study From Wilsonville, Oregon, United States. Issue 5 (19th June 2021) - Hatfield, Richard G; Strange, James P; Koch, Jonathan B; Jepsen, Sarina; Stapleton, Isaak
Abstract: In June of 2013 an application of dinotefuran on an ornamental planting of European linden trees ( Tilia cordata Mill. [Malvales: Malvalceae]) in a shopping mall parking lot in Wilsonville, Oregon provoked the largest documented pesticide kill of bumble bees in North America. Based on geographic information systems and population genetic analysis, we estimate that between 45, 830 and 107, 470 bumble bees originating from between 289 and 596 colonies were killed during this event. Dinotefuran is a neonicotinoid that is highly effective in exterminating and/or harming target pest insects and non-target beneficial insects. Analysis to detect the concentration of pesticides in flowers that received foliar application revealed that the minimum reported dinotefuran concentration of a sampled T. cordata flower was 7.4 ppm, or in excess of 737% above the LC50 of the beneficial pollinator, the honey bee ( Apis mellifera Linnaeus, 1758 [Hymenoptera: Apidae]). Furthermore, sampled Vosnesensky bumble bees ( Bombus vosnesenskii Radoskowski, 1862 [Hymenoptera: Apidae]) were found to have an average dinotefuran concentration of 0.92 ppm at the time of death, which exceeds the maximum LC50 of A. mellifera (0.884 ppm). Our study underscores the lethal impact of the neonicotinoid pesticide dinotefuran on pollinating insect populations in a suburban environment. To our knowledge, the documentation and impact of pesticide kills on wild populations of beneficial insects has not been widely reported in the scientific literature. It is likely that the vast majority of mass pesticide kills of beneficial insects across other environments go unnoticed and unreported.